THERMAL VARIATION FOR GROWTH OF ZOOSPORES OF Albugo spp. - Fonseca, Rafaela Souza Alves; Neves, Paula Rodrigues; Lemes, Natanael Marcos; Decloquement, Jennifer; Lima, Milton Luiz da Paz (REVISTA DE AGRICULTURA NEOTROPICAL, 2018)
The objective of this work was to identify the time of the thermal shock that promotes the greater release of zoospores/sporangia. The experiments were carried out with five treatments, varying the thermal variation time (20’, 30’, 40’, 50’ and 60’) of sporangia suspension of 7.105 sporangia mL-1 under 5 °C temperature. The incidence of sporangia germinated by 20 times whose It was evaluated100 units at random, using an optical microscope at 40 times magnification. The F and Tukey test were used to compare the means. The sexual phase (presence of oospores) was identified in the isolate derived from purslane. In purslane leaves (infected by Albugo portulacae) the time of 20-30’ promoted a greater number of zoospores released, whereas for the isolate from amarantus (infected by A. bliti) the time of 30’ promoted statistically the highest release of zoospores; for the isolate from leaves of “jetirana” (infected by A. ipomoeae-panduratae) the time of 30-50’ promoted greater release of zoospores; and finally the isolate from “onze-horas” leaves (infected by A. portulacae) the time of 30-40’ statistically promoted the highest percentage of release of zoospores, It was demonstrating a differential behavior per host in the release of zoospores. The thermal shock time that promoted the highest amount of released zoospores (38 %) was observed for the purslane-Albugo portulacae and “onze horas”-A. portulacae pathosystem.